STRENGTHENING COMMUNITY SOCIAL CAPITAL IN PEATLAND MANAGEMENT - Zulkarnaini, Zulkarnaini; Sujianto, Sujianto; Wawan, Wawan; Muchid, Muchid; Mashur, Dadang (Sosiohumaniora, 2023)
People who live on peatlands are very dependent on the values and functions contained by the surrounding ecosystem. They certainly need empowerment to strengthen their social capital in meeting their needs. This study aims to analyze the importance of strengthening community social capital on peatlands. The research method used is qualitative research to describe and explain the observed conditions. The results showed that the pattern of ecosystem management on peatlands did not involve all parties, so that people living on peatlands did not really feel the benefits. Whereas the existence of the community can be relied on in maintaining the ecosystem even though they have reasons to use existing resources to fulfill their daily needs. It is just a matter of how all stakeholders involved can make efforts to empower them so that they have strong social capital to protect the environment. With this, the community will feel they have an interest in using all available resources on peatlands in a responsible and sustainable manner.